I Am Not a Tractor! : How Florida Farmworkers Took On the Fast Food Giants and Won - Marquis, Susan L. (Susan Lynn), 1960- (Book collections on Project MUSE., 2017)
"I am Not a Tractor! celebrates the courage, vision, and creativity of the farmworkers and community leaders who have transformed one of the worst agricultural situation in the United States into one of the best. Susan Marquis highlights past abuses workers suffered in Florida's tomato fields: toxic pesticide exposure, beatings, sexual assault, rampant wage theft, and even, astonishingly, modern-day slavery. Marquis unveils how, even without new legislation, regulation, or government participation, these farmworkers have dramatically improved their work conditions. Marquis credits this success to the immigrants from Mexico, Haiti, and Guatemala who formed the Coalition of Immokalee Workers, a neuroscience major who takes great pride in the watermelon crew he runs, a leading farmer/grower who was once homeless, and a retired New York State judge who volunteered to stuff envelopes and ended up building a ground-breaking institution. Through the "Fair Food Program" that they have developed, fought for, and implemented, these people have changed the lives of more than thirty thousand field workers. I Am Not a Tractor! offers a range of solutions to a problem that is rooted in our nation's slave history and that is worsened by ongoing conflict over immigration"--